The hundred dresses - Estes, Eleanor, 1906-1988.; Slobodkin, Louis, 1903-1975 (New York, Harcourt Brace Jovanovich, 1944)
In winning a medal she is no longer there to receive, a tight-lipped little Polish girl teaches her classmates a lesson.
G6
Keywords: Polish Americans -- Fiction; Friendship -- Fiction